The Role of Railways in the Ottoman Empire During the First World War - Cosar, Nevin; Doygun, Ecem; Demirci, Sevtap (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Some of the most important factors influencing the course and outcome of the First World War were the strength of national economies, mobilization of the army, and the supply of basic products and military supplies. The railway networks played a strategic role in the war. The Ottoman Empire joined the Central Powers in the First World War in November 1914. Due to the war conditions in each country and the destruction of the railway network in Serbia, the expected level of imports could not be reached in the first 2 years. The capital city dwellers particularly experienced serious shortages of staple products during the war. The purpose of this article is to shed light on the role of railways in the Ottoman Empire during the First World War. The article examines the role of the Edirne-Istanbul railways in the battle of Gallipoli and also the provision of goods to Istanbul during the war.
Keywords: Area Studies